Pengaruh Current Ratio (CR), Debt To Equity Ratio (DER), Cash Turnover (Perputaran Kas), Total Asset Turnover (TATO) Terhadap Profitabilitas Pada Perusahaan Barang Konsumsi Yang Terdaftar Di Bursa Efek Indonesia Periode 2018-2021 - Nanci Tesalonika Sianturi; Kristina Limbong; Keumala Hayati; Munawarah Munawarah (Journal of Economic, Bussines and Accounting (COSTING), 2023)
This study examines the impact of the Debt to Equity Ratio, Current Ratio, Cash Turnover, and Total Assets Turnover on the profitability of consumer goods industry companies on the IDX 2018-2021. Independent variable (X), namely: Current Ratio, Debt to Equity Ratio, Cash Turnover, and Total Assets Turnover. The dependent variable (Y): Profitability (Return On Assets/ ROA). The sample through purposive sampling resulted in 34 companies. The analytical method uses multiple linear regression methods. The results of the study state that through a simultaneous method, the Debt to Equity Ratio, Current Ratio, Cash Turnover, and Total Assets Turnover have a significant and positive impact on Profitability. Partially, Current Ratio, Cash Turnover, and Total Assets Turnover do not have a significant impact on Profitability, while DER partially has a positive and insignificant impact on Profitability. The test results for the coefficient of determination yield an R2 value of 0.323 meaning that 32.3% of the profitability variable for consumer goods companies which are listed on the IDX 2018-2021 can be described through Current Ratio (X1), Debt to Equity Ratio (X2), Cash Turnover (X3), and Total Assets Turnover (X4). Then the remaining 67.7% can be clarified through other variables which were not tested in this study. Keywords: Debt to Equity Ratio, Current Ratio, Cash Turnover, Total Assets Turnover, and Profitability